An analysis of spatial patterns of toponyms in Guangdong, China. Issue 2 (3rd May 2016) - Qian, Siwei; Kang, Mengjun; Wang, Mingjun
ABSTRACT: The unique geographical environment and the historical waves of immigration of the northern Han Chinese to the Lingnan region have contributed to the development of a complex and unique culture in Guangdong Province. Four ancient ethnic groups, the Zhuang, Cantonese, Hoklo and Hakka, have resided in this area for centuries. As an important part of local culture, toponyms often survive changes in history and can reveal the temporal differences between the past and present in landforms and the spatial differences in the distribution of different ethnic group populations. In this study, two goals were sought: (1) the adoption of spatial smoothing and interpolation methods to reveal the spatial patterns of the Zhuang, Cantonese, Hoklo and Hakka toponyms based on comparisons among the proportions of those who speak various languages and (2) the investigation of the differences among toponymic layers under regional environmental conditions and the influences of geographic factors using an independent samples t -test and a binary logistic regression.